Teaching-Learning in mathematics and statistics during COVID-19. Universidad de los Llanos, Colombia (2021)
Objective: to present the educational experiences of students and teachers on the remote learning model implemented by the University during the COVID-19 lockdown. This is a case study based on the intersemester courses offered by the Department of Mathematics and Physics of the Universidad de los Llanos Colombia.   Originality/contribution: to document the historical lockdown, caused by the COVID-19 pandemic, with respect to the first experiences but also the social and educational problems faced by higher education institutions, such as the implementation of a remote learning model to ensure the continuity of the educational process.   Method: it was used a mixed descriptive methodological approach. Content analysis was carried out with the instruments applied to the participants -students enrolled in the intersemester courses of Special Mathematics and Experimental Design-.   Strategies/information collection: The collection strategy for this research was carried out in two stages. First, a questionnaire was applied to characterize the study population and to learn about the social responsibility and the impact of the pandemic. Secondly, with the purpose of gathering information on the perception, difficulties, advantages and disadvantages of the online modality of the inter-semester courses, two instruments were applied; one was addressed to the students who finished their courses and the other to the dropouts.   Conclusions: From these first shared experiences, it can be concluded that there was consensus around the idea of remote education as an alternative to give continuity to the learning process, but it was noted that its implementation and development require more time and work. The dynamism offered by ICTs was revalued, as they became a mechanism of mandatory applicability in the teaching-learning process. Likewise, the inter-semester courses externalized the inequality and segregation of the region and among its students because only a small group equipped with the necessary technological and connectivity resources benefited from this modality.